The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/su15021344
|View full text |Cite
|
Sign up to set email alerts
|

Construction Techniques and Detailing for Romanian Paiantă Houses: An Engineering Perspective

Abstract: Traditional houses represent landmarks of local cultures all over the world. In seismically prone countries, the traditional timber frames with different types of infills have shown quite good earthquake resilience, an essential feature considering their large number, their simplicity and their reduced cost, owing to the use of local materials and workmanship. In fact, their seismic behavior fostered the interest in further scientific research, including that addressing engineering aspects. Because of their di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Another explanation for this is the older age of the barn-dwellings. Our findings are supported by Dutu et al (2023), who showed that the most of the damage and degradations that occur in almost all traditional timber houses are related to water infiltrations and humidity -the wall, roof and foundation are in contact with the highest moisture loads. Although houses with a different basic typology, these structures have been determined also by other studies to be the most vulnerable.…”
Section: Studied Houses and The Main Vulnerable Structuressupporting
confidence: 87%
“…Another explanation for this is the older age of the barn-dwellings. Our findings are supported by Dutu et al (2023), who showed that the most of the damage and degradations that occur in almost all traditional timber houses are related to water infiltrations and humidity -the wall, roof and foundation are in contact with the highest moisture loads. Although houses with a different basic typology, these structures have been determined also by other studies to be the most vulnerable.…”
Section: Studied Houses and The Main Vulnerable Structuressupporting
confidence: 87%